(8y + 17) = (6x - 7)
(3x -29) + (6x -7) = 180
9x -36 = 180
9x = 216
x = 24
(8y + 17) = (6x - 7)
8y + 17 = 6(24) - 7
8y + 17 = 144 -7
8y = 120
y = 15
I hope this helps!! (and hope it’s correct hahah :))
1. First of all arrange the data set in either ascending or descending order.
12, 19, 24, 26, 31, 38, 53. N = 7 (number of data items)
Median position = 1/2(N + 1)th item = 1/2(7 + 1)th item = 1/2(8)th item = 4th item = 26
First quatile = 1/4(N + 1)th item = 1/4(7 + 1)th item = 1/4(8)th item = 2nd item = 19
Third quatile = 3/4(N + 1)th item = 3/4(7 + 1)th item = 3/4(8)th item = 6th item = 38
Interquatile range = Third quartile - first quatile = 38 - 19 = 19
Answer:
Your answer is option C … (-5, -1, 0)
Step-by-step explanation:
![\bold{\huge{\pink{\underline{ Solution }}}}](https://tex.z-dn.net/?f=%5Cbold%7B%5Chuge%7B%5Cpink%7B%5Cunderline%7B%20Solution%20%7D%7D%7D%7D)
![\bold{\underline{ Given }}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cunderline%7B%20Given%20%7D%7D)
- <u>We </u><u>have </u><u>given </u><u>two </u><u>linear </u><u>equations </u><u>that</u><u> </u><u>is </u><u>2x </u><u>-</u><u> </u><u>3y </u><u>=</u><u> </u><u>-</u><u>6</u><u> </u><u>and </u><u>x</u><u> </u><u>+</u><u> </u><u>3y </u><u>=</u><u> </u><u>1</u><u>2</u><u> </u><u>.</u>
![\bold{\underline{ To \: Find }}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cunderline%7B%20To%20%5C%3A%20Find%20%7D%7D)
- <u>We </u><u>have </u><u>to </u><u>find </u><u>the </u><u>value </u><u>of </u><u>x </u><u>and </u><u>y </u><u>by </u><u>elimination </u><u>method</u><u>. </u>
![\bold{\underline{ Let's \: Begin }}](https://tex.z-dn.net/?f=%5Cbold%7B%5Cunderline%7B%20Let%27s%20%5C%3A%20Begin%20%7D%7D)
![\sf{ 2x - 3y = -6 ...eq(1)}](https://tex.z-dn.net/?f=%5Csf%7B%202x%20-%203y%20%3D%20-6%20...eq%281%29%7D)
![\sf{ x + 3y = 12 ...eq(2)}](https://tex.z-dn.net/?f=%5Csf%7B%20x%20%2B%20%203y%20%3D%2012%20...eq%282%29%7D)
<u>Multiply </u><u>eq(</u><u> </u><u>2</u><u> </u><u>)</u><u> </u><u>by </u><u>2</u><u> </u><u>:</u><u>-</u>
![\sf{ 2( x + 3y = 12 )}](https://tex.z-dn.net/?f=%5Csf%7B%202%28%20x%20%2B%203y%20%3D%2012%20%29%7D)
![\sf{ 2x + 6y = 24 }](https://tex.z-dn.net/?f=%5Csf%7B%202x%20%2B%206y%20%3D%2024%20%7D)
<u>Subtract </u><u>eq(</u><u>1</u><u>)</u><u> </u><u>from </u><u>eq(</u><u>2</u><u>)</u><u> </u><u>:</u><u>-</u>
![\sf{ 2x + 6y -( 2x - 3y) = 24 -(-6)}](https://tex.z-dn.net/?f=%5Csf%7B%202x%20%2B%206y%20-%28%202x%20-%203y%29%20%3D%2024%20-%28-6%29%7D)
![\sf{ 2x + 6y - 2x + 3y = 24 + 6 }](https://tex.z-dn.net/?f=%5Csf%7B%202x%20%2B%206y%20-%202x%20%2B%203y%20%3D%2024%20%2B%206%20%7D)
![\sf{ 9y = 30 }](https://tex.z-dn.net/?f=%5Csf%7B%20%20%209y%20%3D%2030%20%7D)
![\sf{ y = 30/9}](https://tex.z-dn.net/?f=%5Csf%7B%20%20%20y%20%3D%2030%2F9%7D)
![\sf{\red{ y = 10/3}}](https://tex.z-dn.net/?f=%5Csf%7B%5Cred%7B%20y%20%3D%2010%2F3%7D%7D)
<u>Now</u><u>, </u><u> </u><u>Subsitute</u><u> </u><u>the </u><u>value </u><u>of </u><u>y </u><u>in </u><u>eq(</u><u> </u><u>1</u><u> </u><u>)</u><u>:</u><u>-</u>
![\sf{ 2x - 3(10/3) = -6 }](https://tex.z-dn.net/?f=%5Csf%7B%202x%20-%203%2810%2F3%29%20%3D%20-6%20%7D)
![\sf{ 2x - 10 = -6 }](https://tex.z-dn.net/?f=%5Csf%7B%202x%20-%2010%20%3D%20-6%20%7D)
![\sf{ 2x = -6 + 10}](https://tex.z-dn.net/?f=%5Csf%7B%202x%20%20%3D%20-6%20%2B%2010%7D)
![\sf{ x = 4/2}](https://tex.z-dn.net/?f=%5Csf%7B%20x%20%20%3D%204%2F2%7D)
![\sf{\red{ x = 2}}](https://tex.z-dn.net/?f=%5Csf%7B%5Cred%7B%20x%20%20%3D%202%7D%7D)
Hence, The value of x and y is 2 and 10/3
You would have none left. If you started with one cup of cornmeal and then you used that one cup of cornmeal to make the muffins, you would have none left